2022
DOI: 10.21037/tcr-21-2506
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B for predicting the durable clinical benefit of anti-PD-1/PD-L1 immunotherapy in patients with non-small cell lung cancer

Abstract: Background: To identify immunotherapy biomarkers, we examined granzyme B levels in peripheral blood PD-1 + CD8 + T cells and their relationship with treatment outcomes in patients with non-small cell lung cancer (NSCLC).Methods: To evaluate the association of granzyme B with response to immunotherapy, we tested blood samples obtained from 16 patients with stage IIIC to IV NSCLC receiving immune-checkpoint inhibitor treatment. We used flow cytometry to measure the change in the percentage of PD1 + CD8 + T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It has been shown that high GZMB is associated with the increased cytotoxic activity of tumor‐infiltrating lymphocytes (TILs) and improved disease‐free survival (DFS) and OS in multiple cancer types. 62 , 63 However, GZMB expression alone or coupled with markers like PD‐L1 can variably affect both recurrence‐free survival (RFS) and OS. 62 , 64 , 65 Our study supports these contradictory data by demonstrating that high GZMB expression is linked with poor survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that high GZMB is associated with the increased cytotoxic activity of tumor‐infiltrating lymphocytes (TILs) and improved disease‐free survival (DFS) and OS in multiple cancer types. 62 , 63 However, GZMB expression alone or coupled with markers like PD‐L1 can variably affect both recurrence‐free survival (RFS) and OS. 62 , 64 , 65 Our study supports these contradictory data by demonstrating that high GZMB expression is linked with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis for the stroma confirms the unfavorable impact of LAG3, B7‐H3 and PDL1, implying that when other covariates are controlled, the adverse effects of these markers become more pronounced. It has been shown that high GZMB is associated with the increased cytotoxic activity of tumor‐infiltrating lymphocytes (TILs) and improved disease‐free survival (DFS) and OS in multiple cancer types 62,63 . However, GZMB expression alone or coupled with markers like PD‐L1 can variably affect both recurrence‐free survival (RFS) and OS 62,64,65 .…”
Section: Discussionmentioning
confidence: 99%
“…GZMB is associated with liver cancer progression [ 6 ] and is a potential prognostic marker of colorectal cancer [ 7 ]. Furthermore, serial changes in GZMB expression in non-small-cell lung cancer may serve as a biomarker for monitoring monotherapy with immune checkpoint inhibitors [ 8 , 9 ]. In breast cancer immunotherapy, the role of GZMB in the tumor microenvironment is also important [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of granzyme B nanoparticles and positron emission tomography imaging has enabled us to quantitatively detect responsiveness to immunotherapy in accordance with tumor volume reduction (13). Previously, we also reported that the measurement of granzyme B levels in blood samples from patients with lung cancer could predict immunotherapy outcomes (14). Interestingly, the number of granzyme B-secreting NK T-like, NK, and CD8 + T cells and their granzyme B contents are decreased in lung cancer tissues compared to those in non-lung cancer tissues (15,16).…”
Section: Introductionmentioning
confidence: 99%